Abnormal hubs in global network as neuroimaging biomarker in right temporal lobe epilepsy at rest - Guo, Ruimin; Zhao, Yunfei; Jin, Honghua; Jian, Jihua; Wang, Haibo; Jin, Shengxi; Ren, Hongwei (Frontiers in Psychiatry, 2022)
While abnormal neuroimaging features have been reported in patients suffering from right temporal lobe epilepsy (rTLE), the value of altered degree centrality (DC) as a diagnostic biomarker for rTLE has yet to be established. As such, the present study was designed to examine DC abnormalities in rTLE patients in order to gauge the diagnostic utility of these neuroimaging features. In total, 68 patients with rTLE and 73 healthy controls (HCs) participated in this study. Imaging data were analyzed using DC and receiver operating characteristic (ROC) methods. Ultimately, rTLE patients were found to exhibit reduced right caudate DC and increased left middle temporal gyrus (MTG), superior parietal gyrus (SPG), superior frontal gyrus (SFG), right precuneus (PCu), frontal gyrus Inferior gyrus (IFG), middle-superior frontal gyrus (MSFG), and inferior parietal gyrus (IPG) DC relative to HC. ROC analyses indicated that DC values in the right caudate nucleus could be used to differentiate between rTLE patients and HCs with a high degree of sensitivity and specificity. Together, these results thus suggest that rTLE is associated with abnormal DC values in the right caudate nucleus, underscoring the relevance of further studies of the underlying pathophysiology of this debilitating condition.